2014
DOI: 10.1016/j.ijnss.2014.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Preferred and actual participation roles in operation treatment decision making of patients with colorectal cancer

Abstract: a b s t r a c tPurpose: To investigate the preferred and actual participation levels of colorectal cancer patients and their families in treatment decision-making. Methods:A cross-sectional survey was conducted using a questionnaire administered to colorectal cancer patients hospitalized in the general surgical wards in two of the upper first-class hospitals in Beijing between February and July 2013.Results: A total of 113 questionnaires were analyzed. For the families of colorectal cancer patients, the concor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…More educated patients are also much more likely to adopt new ideas and behaviors, such as the new health technology in their disease treatment. All of these relationships in this study are consistent with previous reports investigating the impact of patient demographic characteristics, and clinical decisions (3840) on their participation and SDM score. Patients were very satisfied with the process of decision making, especially those who had much higher SDM-Q-9 scores indicated they had better involvement in the decision making and closer communication with their treating physician.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…More educated patients are also much more likely to adopt new ideas and behaviors, such as the new health technology in their disease treatment. All of these relationships in this study are consistent with previous reports investigating the impact of patient demographic characteristics, and clinical decisions (3840) on their participation and SDM score. Patients were very satisfied with the process of decision making, especially those who had much higher SDM-Q-9 scores indicated they had better involvement in the decision making and closer communication with their treating physician.…”
Section: Discussionsupporting
confidence: 92%
“…Patients also thought that physicians and patients reached an agreement on whether and how to adopt a new health technology. This could also explain a higher proportion of study respondents who preferred an SDM role, compared with those reported in the previous studies focusing on the Chinese population, ranging from 24.80 to 65.00 percent (37, 38). The higher preference on SDM may be due to the study hospitals being located in Eastern China, a region with high economic development and higher awareness for better patient participation than other regions.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…All 32 included publications had a cross‐sectional study design, 11 of which derived their patient population from previous cohort studies, or from the control group of a randomized trial. Twenty of the 32 studies were published after 2010, 11 between 2000 and 2010, and one in 1989.…”
Section: Resultsmentioning
confidence: 99%
“…The questionnaire which was used to evaluate the patients’ involvement in TDM was adopted from the current relevant literature on this subject (Hou, Pang, Lu, Xu, & Zhou, ; Sekimoto et al., ; Shin et al., ). The questionnaire comprised of three parts: the patients’ socio‐‎demographic data; the medical and ‎family history of the patients; and an evaluation of the patient's experiences of, and preferences for, their family's involvement levels in TDM.…”
Section: Methodsmentioning
confidence: 99%